Discursive Configurations About the Francophone World and the French Language in Colombian Written Press - Lamprea-Abril, Nathalia (Íkala, Revista de Lenguaje y Cultura, 2023)
The notion of francophonie still raises many questions in various fields, such as the didactic, economic, political, and media fields, among others, making it difficult to understand the concept. In this article, we analyze the ways in which the discursive contours of the francophone issue and its representation in the discourse of the Colombian print media are defined, based on a corpus of 35 journalistic articles. To this end, we combined textometric analyses obtained with the Iramuteq® software with linguistic discourse analysis tools, in order to propose an interpretative hypothesis. On this basis, we were able to demonstrate that, in the Colombian print media, the issue of francophonie is mainly elaborated on the basis of its relationship to the French language and, more concretely, on the basis of its pragmatic aim, which configures a discursive register of education and work. In addition, there is a quest linked to the desire for social mobility, where language takes on the role of auxiliary, even in the absence of cultural, social, political or historical dimensions. From this point of view, its learning and its use are reduced to a rather technical and individual subject without considering its complex character also constituting the social.